H24

So sánh:

   A=\(\frac{2015^{2013}+1}{2015^{2014}+1}\)

    B=\(\frac{2015^{2015}+1}{2015^{2016}+1}\)

NK
22 tháng 2 2016 lúc 22:47

\(A=\frac{2015^{2013}+1}{2015^{2014}+1}=\frac{\left(2015^{2013}+1\right)\left(2015^{2014}+1\right)}{\left(2015^{2014}+1\right)\left(2015^{2016}+1\right)}=\frac{2015^{4027}+2015^{2013}+2015^{2014}+1}{\left(2015^{2014}+1\right)\left(2015^{2016}+1\right)}\)

\(B=\frac{2015^{2015}+1}{2015^{2016}+1}=\frac{\left(2015^{2015}+1\right)\left(2015^{2014}+1\right)}{\left(2015^{2016}+1\right)\left(2015^{2014}+1\right)}=\frac{2015^{4029}+2015^{2015}+2015^{2014}+1}{\left(2015^{2016}+1\right)\left(2015^{2014}+1\right)}\)

Ta thấy hiển nhiên thử của B > tử của A nên B > A

Vậy...

Bình luận (0)

Các câu hỏi tương tự
TT
Xem chi tiết
H24
Xem chi tiết
NH
Xem chi tiết
TH
Xem chi tiết
HN
Xem chi tiết
NT
Xem chi tiết
BA
Xem chi tiết
ND
Xem chi tiết
PN
Xem chi tiết